Decline in lizard species diversity, abundance and ectoparasite load across an elevational gradient in the Australian alps. (6th September 2020) - Hamilton, Katelyn; Goulet, Celine T.; Drummond, Emily M.; Senior, Anna F.; Schroder, Mellesa; Gardner, Michael G.; While, Geoffrey M.; Chapple, David G.
Abstract: The rapid changes in altitude, and associated habitat, of mountain ecosystems make them ideal natural laboratories for testing the effect of environmental heterogeneity on species assemblage. Our understanding of the sensitivity of Australian reptiles to elevational clines is limited. We examined lizard distribution across three elevation zones (montane, subalpine and alpine), spanning from 900 to 1840 m above sea level, in the Australian alps. We aimed to examine how elevation influences species diversity and abundance, and ectoparasite load, and whether species alter their habitat use amongst different elevational zones. Active searches were conducted across the elevation zones to identify lizard community structure (at least 16 species) across elevational zones, along with skink habitat preferences and the ectoparasite load. Skink diversity and abundance were negatively correlated with increased elevation. The alpine zone had significantly lower diversity and abundance of skinks. Habitat use differed amongst both elevations and species. Ectoparasite prevalence was also significantly diminished in the alpine zone. Ectoparasites only infected a subset of the skink community, with ectoparasite load increasing as the active season progressed. This study provides evidence of the complex interplay between elevation and species diversity, as well as the differences in ectoparasite pressure along elevational gradients in the Australian alps.